Model Development for the Prediction of the Resilient Modulus of Warm Mix Asphalt - Huda Mahdi Saleh; Amjad H. Albayati (Salehan Institute of Higher Education, 2020)
Increasing material prices coupled with the emission of hazardous gases through the production and construction of Hot Mix Asphalt (HMA) has driven a strong movement toward the adoption of sustainable construction technology. Warm Mix Asphalt (WMA) is considered relatively a new technology, which enables the production and compaction of asphalt concrete mixtures at temperatures 15-40 °C lower than that of traditional hot mix asphalt. The Resilient modulus (Mr) which can be defined as the ratio of axial pulsating stress to the corresponding recoverable strain, is used to evaluate the relative quality of materials as well as to generate input for pavement design or pavement evaluation and analysis. Based on the aforementioned preface, it is possible to conclude that there is a real need to develop a predictive model for the resilient modulus of the pavement layer constructed using WMA. Within the experimental part of this study, 162 cylindrical specimens of WMA were prepared with dimensions of 101.6 mm in diameter and 63.5 mm in thickness. The specimens were subjected to the indirect tension test by pneumatic repeated loading system (PRLS) to characterize the resilient modulus. The test conditions (temperature and load duration) as well as mix parameters (asphalt content, filler content and type, and air voids) are considered as variables during the specimen’s preparation. Following experimental part, the statistical part of the study includes a model development to predict the Mr using Minitab vs 17 software. The coefficient of determination (R2) is 0.964 for the predicted model which is referred to a very good relation obtained. The Mr value for the WMA is highly affected by the temperature and moderately by the load duration, whereas the mix parameters have a lower influence on the Mr.